Research, management, and conservation of the yellow-shouldered Amazon (Amazona barbadensis) across its range in the southern Caribbean and mainland Venezuela: 1980s to the present - Briceño-Linares, José Manuel; Aranguren-Alvarez, Jesús; Clarenda, Julianka; Díaz, Alejandro; Doest, Odette; Haines, Jack; Houtepen, Erik; Martin, Rowan O.; Millán, Pablo Antonio; Nunes, Giancarlo; Schmaltz, Lauren; Sucre, Bibiana; et al. (Frontiers in Conservation Science, 2024)
The yellow-shouldered Amazon (Amazona barbadensis) has been the object of a decentralized research and conservation program throughout its range, spanning mainland Venezuela, the Venezuelan islands of La Blanquilla and Margarita, and Aruba, Curaçao and Bonaire in the Southern Caribbean. Multiple interventions have been implemented since the 1980s, primarily in Bonaire and Margarita, including nest protection, the provision of artificial nests, predator control, health monitoring, ecosystem restoration, community education and awareness building. As a result, fledgling recruitment in these two locations has increased and populations have grown substantially. In this article, we summarize the interventions and their impact on population abundance and poaching of nestlings. The status of populations in the Venezuelan mainland continues to be uncertain -yellow-shouldered Amazons were observed recently in their historical distribution, but poaching is still widespread. A 2024 reintroduction in Aruba was the first step toward reestablishment of parrots in the island after being extirpated around 1950. Building on four decades of experience and work, a range wide action plan calls for achieving the vision that by 2031 Amazona barbadensis has functional, viable wild populations throughout its historical range.Steps taken to date suggest that this is within reach if past successes can be sustained and replicated elsewhere, particularly in mainland Venezuela.